2010
DOI: 10.1177/039463201002300427
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profiling of Oral Carcinoma Identifies New Markers of Tumor Progression

Abstract: Oral squamous cell carcinoma, the most frequently occurring malignant head and neck tumour, generally exhibits poor prognosis and metastases are the main cause of death. The discovery of reliable prognostic indicators of tumour progression could greatly improve clinical practice. MicroRNAs are involved in the regulation of basic cellular processes such as cell proliferation, differentiation, and apoptosis. Since miRNAs have been shown to be abnormally expressed in different tumours their importance as potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
160
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(173 citation statements)
references
References 26 publications
10
160
0
3
Order By: Relevance
“…In this study, we showed that RASSF5 expression was significantly decreased in oral cancer tissues, consistent with results of a previous study showing down-regulation of RASSF5 expression in 54 cases of head and neck cancer patients, including oral cancer (Steinmann et al, 2009). Moreover, we also observed elevated expression levels of miR-214 in oral cancer tissues, consistent with another study (Scapoli et al, 2010). Unsurprisingly, miR-214 levels were reported to be significantly elevated in cisplatin resistant tongue squamous carcinoma cell line Tca/cisplatin compared to those in cisplatin sensitive Tca8113, indicating the role of miR-214 in tumor promotion in oral cancer (Yu et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we showed that RASSF5 expression was significantly decreased in oral cancer tissues, consistent with results of a previous study showing down-regulation of RASSF5 expression in 54 cases of head and neck cancer patients, including oral cancer (Steinmann et al, 2009). Moreover, we also observed elevated expression levels of miR-214 in oral cancer tissues, consistent with another study (Scapoli et al, 2010). Unsurprisingly, miR-214 levels were reported to be significantly elevated in cisplatin resistant tongue squamous carcinoma cell line Tca/cisplatin compared to those in cisplatin sensitive Tca8113, indicating the role of miR-214 in tumor promotion in oral cancer (Yu et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…MiRNAs have been receiving increasing attention for their role in oral cancer (Manikandan et al, 2016). MiR-214 levels were revealed to be up-regulated in oral cancer tissues, indicating that miR-214 might be an oncogene involved in oral cancer (Scapoli et al, 2010). Furthermore, bioinformatics analysis demonstrated that miR-214 could bind to the 3'-UTR of RASSF5.…”
Section: Introductionmentioning
confidence: 99%
“…However, decreased miR-132 expression has been observed in osteosarcoma (26) and liver cancer (27). Increased miR-212 expression was reported in oral squamous cell carcinoma (28) and colorectal carcinoma (23), and miR-212 has been shown to be downregulated in gastric cancer (29), NSCLC (30) and head and neck squamous cell carcinoma (31). The different levels of expression of these miRNAs in various cancers indicate that they may exert diverse functions in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation increases production of inflammatory cytokines and reactive oxygen species and DNA damage, and results in development and progression of carcinomas (Meira et al, 2008). Oral carcinoma cells upregulate the E-cadherin-targeting miR-92 (Scapoli et al, 2010). Although expression of miR-200 in OSCCs is not known at present, nasopharyngeal carcinomas downregulate it which destabilizes ZEB1/2 mRNA (Chen et al, 2009).…”
Section: Loss Of E-cadherin Expression In Oral Squamous Cell Carcinomasmentioning
confidence: 99%